Spin-off and its impact on the third party funds of Indonesian Islamic banking industry - M. Nur Rianto Al Arif (Universitas Islam Indonesia, 2014)
The purpose of this paper is to examine the spin-off policy based on Islamic Banking Act No. 21/2008 had an impact on the third party fund of Islamic banking industry in Indonesia. This research used ordinary least square regression consisting dummy variable of spin-off, deposit margin, non-performing financing (NPF), efficiency ratio (BOPO), and profitability ratio (ROA). The result showed that all the independent variables had an impact on the third party funds in Indonesian Islamic banking industry. The implication of this result is spin-off policy had a good impact on the growth of third party funds in Indonesian Islamic banking industry.